2018
DOI: 10.1038/mi.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A negatively regulates lymphangiogenesis in T helper 17 cell-mediated inflammation

Abstract: During inflammation lymphatic vessels (LVs) are enlarged and their density is increased to facilitate the migration of activated immune cells and antigens. However, after antigen clearance, the expanded LVs shrink to maintain homeostasis. Here we show that interleukin (IL)-17A, secreted from T helper type 17 (T17) cells, is a negative regulator of lymphangiogenesis during the resolution phase of T17-mediated immune responses. Moreover, IL-17A suppresses the expression of major lymphatic markers in lymphatic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
(66 reference statements)
0
12
0
2
Order By: Relevance
“…CD4 + T cell, CD8 + T cell, ILCs, CD4 − CD8 − T cells, γ δT cells, iNK T cells, NK cells, neutrophils, and mast cells) secrete IL17A, [21][22][23][24][25][26][27][28][29][30][31] which contributes to many autoimmune disorders in humans. 8,[12][13][14][15][16][17][18][19] Thus, IL17A secretion by many of the immune cells listed above suggests that the pathology associated with these cell types could be due to IL17A producing cells. IL17A binds to IL17RA and IL17RC receptors to form a heterodimer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CD4 + T cell, CD8 + T cell, ILCs, CD4 − CD8 − T cells, γ δT cells, iNK T cells, NK cells, neutrophils, and mast cells) secrete IL17A, [21][22][23][24][25][26][27][28][29][30][31] which contributes to many autoimmune disorders in humans. 8,[12][13][14][15][16][17][18][19] Thus, IL17A secretion by many of the immune cells listed above suggests that the pathology associated with these cell types could be due to IL17A producing cells. IL17A binds to IL17RA and IL17RC receptors to form a heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of our study, the IL17 pathway has been shown to play a pathogenic role in many human autoimmune diseases, including psoriasis, RA, MS, and inflammatory bowel disease. 8,[12][13][14][15][16][17][18][19] Recently, fever induced T H 17 cells were also shown to induce expression of transcription factors involved in induction of EAE. 86 IL17 is also known to have a negative effect on the proliferation of hepatitis B virus-related hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism by which IL-17 induces VEGF-D/C remains unclear, pathways involving direct upregulation of VEGF-D by IL-17 receptor-expressing cells such as corneal epithelial and stromal cells and indirect upregulation of VEGF-C through IL-1β-mediated pathways are suspected [ 55 , 60 ]. However, IL-17 has recently been reported as a negative regulator of lymphangiogenesis during the resolution phase of Th17-mediated immune responses in a model of cholera toxin-mediated lung inflammation [ 61 ], suggesting that the effect of IL-17 on lymphangiogenesis may differ depending on the organ or situation.…”
Section: Cytokines and Molecular Markers For Lymphangiogenesismentioning
confidence: 99%